Improving the Cultural Responsiveness of Prospective Social Studies Teachers: An Action Research - TUNCEL, GÜL (EDAM, 2017)
In recent years, studies on teacher training have focused on the development of a culturally responsive understanding in prospective teachers and its use to allow students benefit from learning-teaching environments in the best way possible. Considering diverse cultural and linguistic backgrounds of students as wealth is a prerequisite for teachers to create a happy and motivated learning environment for students. Social studies teachers in particular need to become culturally responsive individuals during higher education. The research problem of the present study is How can we ensure prospective teachers become culturally responsive individuals? This study, conducted within the scope of the course Communication and Human Relations with third-year prospective social studies teachers, was planned as an action research. The resulting data were subjected to content analysis. Creating action plans allowed prospective teachers get to know their own culture, learn about the cultural backgrounds of their students, gain a better understanding of social, economic, and political contexts, and improve their skills and willingness to use culturally appropriate management strategies and their commitment to create inclusive classrooms, which are among the elements of culturally responsive teaching.
Keywords: Teacher training; Social studies teacher; Cultural sensitivity; Culture-sensitive teacher; Action research; EDUCATION; STUDENTS